Biomarkers in psoriatic arthritis: a systematic literature review. (2nd June 2016) - Generali, Elena; Scirè, Carlo A.; Favalli, Ennio G.; Selmi, Carlo
ABSTRACT: Psoriatic arthritis (PsA) is characterized by chronic inflammation of peripheral joints and axial skeleton, associated with a strong genetic background. Clinics include enthesitis or dactylitis and extra-articular involvement as uveitis or inflammatory bowel disease, while treatment options range from nonsteroidal anti-inflammatory drugs (NSAIDs) to biologics, targeting TNF α or Th17. No serum autoantibody is associated with PsA, while other biomarkers have been proposed for early diagnosis or to predict treatment response. To better discuss this area of growing interest we performed a systematic review of the literature on biomarkers in PsA. Our research retrieved 408 papers, and 38 were included in the analysis. Based on the available literature, we draw some recommendations for the use of biomarkers in the management of patients with PsA.